2021
DOI: 10.1016/j.amjcard.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Presentation and Outcome of Consecutive Patients Admitted to Hospital Due to ST-Elevation Myocardial Infarction

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The last two years have unexpectedly brought another threat -related to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. As reported by the latest registers from around the world, the incidence of OHCA increased significantly during the pandemic [32,[34][35][36][37][38][39]. Moreover, performed meta-analyzes demonstrated that not only the incidence but also mortality following OHCA were higher during the COVID-19 pandemic [32,33,40].…”
Section: Discussionmentioning
confidence: 97%
“…The last two years have unexpectedly brought another threat -related to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. As reported by the latest registers from around the world, the incidence of OHCA increased significantly during the pandemic [32,[34][35][36][37][38][39]. Moreover, performed meta-analyzes demonstrated that not only the incidence but also mortality following OHCA were higher during the COVID-19 pandemic [32,33,40].…”
Section: Discussionmentioning
confidence: 97%
“…Wienbergen et al, 17 conducted a study to assess the outcomes of patients with STEMI in the year 2020 compared with the years before in a German registry. They included 726 in year 2020 and compared it to 10,226 patients in the years 2006 to 2019 and found that hospital mortality was elevated by 52% compared with the years prior.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and the pandemic-related lockdown and social restriction may have impacted the clinical course of patients treated for acute ST-elevation myocardial infarction (STEMI), although the implications and exact impact are unclear. Information from the database does show, however, that in the year 2020, a highly significant increase of STEMI-patients admitted to hospitals with delayed presentation and poor prognosis was reported 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…They discussed a possible delay by patients, medical services or cardiac catheterization laboratories. Furthermore, Wienbergen et al [ 18 ] showed a significantly higher rate of patients presenting with cardiogenic shock and out-of-hospital cardiac arrest. That may be associated with a delayed presentation in the case of STEMI and may also have contributed to the increased in-hospital mortality demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%